Purification of miraculin from miracle fruit [Synsepalum dulcifium (Schumach. & Thonn.) Daniell] - He, Zuxing (2015)
Synsepalum dulcificum, is a kind of berries, when eaten causes sour foods subsequently consumed to taste sweet. An efficient and low cost purification method to extract this protein needs to be developed. The pure miraculin is needed for characterization and identification of its function prior to commercialization. The potential use of the various parts of miracle fruit as well as the useful components could be extracted also needs to be explored to provide data of the importance of this fruit in economic point of view. The physico-chemical properties of miracle fruit including percentage weight and nutritional elements (ash, crude protein, fat, total dietary fiber, carbohydrate, vitamin A and vitamin C) of miracle fruit were determined to give a full understanding of miracle fruit. Content of total anthocyanin in skin was determined using the pH-differential method. Content of phenolic in seed, skin and pulp was determined by using Folin-Ciocalteau colorimetric method. Antioxidant activity in seed, skin and pulp was analysed by DPPH free radical scavenging method. Study found that vitamin C content (40.1 mg/100 g FW) and total phenolic content (625.57 mg GAE/100 g FW) in miracle fruit flesh are very high and they together contribute to the high antioxidant activity of miracle fruit. At the same time, the sugar content is relatively low (5.6 g/100 g FW) in miracle fruit, making it become a healthy food, especially for the patients of diabetes and obesity, when considering its potential pharmaceutical benefits. Seed oil of miracle fruit was extracted from fine powder seed of miracle fruit using Soxhlet Extractor with petroleum ether. Triacylglycerol profile was determined by HPLC, fatty acid composition was determined by GC analysis after methyl esterification, thermal behavior was determined by Differential Scanning Calorimetry. Triacylglycerol profile and free fatty acid composition showed that the fatty acid in seed oil of miracle fruit was similar to the one of palm oil. Miraculin is a sweet-inducing active protein that comes from miracle fruit and shows many benefits to human. However, optimization of efficient purification method of miraculin from miracle fruit has not been reported in the literature. Immobilized metal ion affinity chromatography (IMAC) with nickel-NTA was employed for miraculin purification from the extract of the pulp with optimization. The effect of extraction buffer on the amount of the extracted total protein was evaluated. This study demonstrated IMAC could be applied as one step process for purification of miraculin. The preferred conditions for high performance of IMAC with nickel-NTA were obtained with the use of crude extract at pH 7, Tri-HCl buffer at pH 7, and 300 mM imidazole with pH 8 used as elution buffer upon. The effect of optimizing crude extract was more important than optimizing the binding buffer. In elution stage, the effect of imidazole was more important than acetic acid. The IMAC charging with nickel was successfully used to purify miraculin from S. dulcificum with the yield and purity of 80.3% and 97.5%, respectively. To reduce the purification cost, the possibility of using reverse micelle extraction (RME) for miraculin purification was also explored. Results from this study have demonstrated that reverse micelle formed by AOT/isooctane system can be applied as simple, convenient and low-cost process for the purification of miraculin from miracle fruit. Different effects for forward extraction and backward stripping were examined. Crude at pH 8 as the aqueous phase and 100 mM AOT/isooctane as the solvent phase during forward extraction; 0.5 M NaCl solution at pH 11, without isopropanol, as the aqueous phase during backward stripping were the optimal conditions to purify miraculin by the RME system. The maximum purification factor, purity and total purified miraculin obtained by RME were 1.63, 94.78% and 41.52 µg/mL, respectively.